Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$a_{n+1} = \frac{1+a_{n}}{3-a_{n}},n\in \mathbb{Z}^{+}$, and $a_{1} = 0$, so how to get the general expression of $a_{n} = ?$

share|cite|improve this question

Hint: have you tried looking at the first few $n$'s? You should see a pattern emerge pretty quickly.

share|cite|improve this answer

As suggested by Robert Israel, let us look at the first terms so we might see a pattern: we have $a_1=0$, $a_2=\frac {1}{3}$, $a_3=\frac {2}{4}$, $a_4=\frac {3}{5}$. All of this suggest $$a_n=\frac{n-1}{n+1}$$

share|cite|improve this answer

Evaluating the first few terms of the sequence: $$a_1=0, a_2=\frac{1}{3}, a_3=\frac{2}{4}, a_4=\frac{3}{5}, a_5=\frac{4}{6}, a_6=\frac{5}{7} \dots$$

So the guess is $a_n=\frac{n-1}{n+1}$. Now let's prove it using induction

Clearly it's true for $n=1$. Assuming the statement is true for $n=k$, i.e. $a_k=\frac{k-1}{k+1}$ $$a_{k+1}=\frac{1+a_k}{3-a_k}=\frac{(k+1)-1}{(k+1)+1}$$

share|cite|improve this answer
I think we disagree. Check my answer, please. Cheers. – Claude Leibovici Apr 13 '14 at 9:57
@ClaudeLeibovici thanks a lot for pointing the error. please note the correction and sorry for not checking. – Sandeep Thilakan Apr 13 '14 at 12:23

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.